Ways to Reduce Financial Risks of Commercial Banks in Modern Conditions on the Example of JSC "Tinkoff Bank" ("Journal "U". Economy. Management. Finance.", 2021)
This article will be of interest to specialists working in the field of risk management, since the purpose of the publication is to analyze the financial risks of commercial banks and ways to reduce them in modern conditions using the example of Tinkoff Bank JSC. The article defines the content of the concepts of "banking risk", its existence not only in the banking sector, but also outside it, "banking risk management", identifies the classification of banking risks and approaches to their assessment. The focus is on combinations of different methods, models, and approaches to reduce the likelihood of risk occurrence. The scientific novelty lies in the consideration of the policy of minimizing the risks of Tinkoff Bank from the point of view of financial management. As a result of the study, the risks that exist for this bank were presented, an analysis of one of them was carried out and a conclusion was drawn about the bank's work with financial risks.
Keywords: bank; banking risks; classification; minimization